2005
DOI: 10.1593/neo.05442
|View full text |Cite
|
Sign up to set email alerts
|

A Population of HLA-DR+ Immature Cells Accumulates in the Blood Dendritic Cell Compartment of Patients with Different Types of Cancer

Abstract: Dendritic cell (DC) defects are an important component of immunosuppression in cancer. Here, we assessed whether cancer could affect circulating DC populations and its correlation with tumor progression. The blood DC compartment was evaluated in 136 patients with breast cancer, prostate cancer, and malignant glioma. Phenotypic, quantitative, and functional analyses were performed at various stages of disease. Patients had significantly fewer circulating myeloid (CD11c+) and plasmacytoid (CD123+) DC, and a conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
44
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 36 publications
7
44
1
1
Order By: Relevance
“…This indicates that the lack of CD80/CD86 expression does not simply result from a lack of activation of these cells in the tumor microenvironment but might be caused by defects in cell differentiation (153). Consistent with these observations, an increased proportion of iDCs with reduced expression of co-stimulatory molecules was found in the peripheral blood of patients with breast, head and neck, lung, and esophageal cancers and similar data has been obtained in mouse tumor models (146)(147)(148)(149)(150)(151)(152)(153)(154). Immature DCs are unable to induce antitumour immune responses and can induce T-cell tolerance.…”
Section: Accumulation Of Immature Dcs In Cancersupporting
confidence: 82%
See 1 more Smart Citation
“…This indicates that the lack of CD80/CD86 expression does not simply result from a lack of activation of these cells in the tumor microenvironment but might be caused by defects in cell differentiation (153). Consistent with these observations, an increased proportion of iDCs with reduced expression of co-stimulatory molecules was found in the peripheral blood of patients with breast, head and neck, lung, and esophageal cancers and similar data has been obtained in mouse tumor models (146)(147)(148)(149)(150)(151)(152)(153)(154). Immature DCs are unable to induce antitumour immune responses and can induce T-cell tolerance.…”
Section: Accumulation Of Immature Dcs In Cancersupporting
confidence: 82%
“…Patients had significantly fewer circulating myeloid DCs and pDC, and a concurrent accumulation of immature DCs. Immature DCs had reduced capacity to capture antigens and elicited poor proliferation and IFN-γ secretion by T-lymphocytes (149). Several clinical studies have provided clear evidence that surgical removal of tumors can increase the number of DCs in the peripheral blood of patients with cancer.…”
Section: Decreased Presence Of Functionally Competent Dcsmentioning
confidence: 99%
“…Despite the reduction of pDC and mature mDC in lymph nodes, we observed an increase in a population of Lin Ϫ HLA-DR mod CD11c Ϫ CD123 Ϫ cells within the Lin Ϫ HLA-DR ϩ fraction of lymph nodes from animals with AIDS that resemble monocytoid cells. Recently, an increased frequency of circulating blood DC lacking CD11c and CD123 expression that elicited poor T cell proliferation and IFN-␥ secretion was identified in cancer patients (55). In our study the Lin Ϫ HLA-DR mod cells did not acquire CD11c or CD123 expression after 24 h of culture, although it is conceivable that a longer period of culture would promote their differentiation.…”
Section: Discussioncontrasting
confidence: 40%
“…In the case of breast cancer, circulating DC have been shown to be numerically reduced (Della Bella et al, 2003), exhibit increased rates of apoptosis (Pinzon-Charry et al, 2005c), and reduced capacity to stimulate T cells (Gabrilovich et al, 1997;Satthaporn et al, 2004). The DC compartment has also been shown to exhibit increased number of immature cells with impaired antigen-presenting capacity (Pinzon-Charry et al, 2005a, d). To date, however, only one -rather small -study has compared blood DC at different stages of disease (Gabrilovich et al, 1997) and no longitudinal studies have been reported.…”
mentioning
confidence: 99%